2000
DOI: 10.1097/00005344-200036051-00117
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers of the Third Generation Inhibit Endothelin-1 Liberation, mRNA Production and Proliferation of Human Coronary Smooth Muscle and Endothelial Cells

Abstract: Endothelin-1 (ET-1) plays an important role in atherogenesis. The aim of the study reported here was to investigate the effects of the third generation beta-blockers nebivolol and carvedilol on ET-1 liberation, preproendothelin-1 production and on proliferation of human coronary cells. Human coronary endothelial (HEC) and smooth muscle cells (HCSMC) were grown with carvedilol or nebivolol (10(-7)-10(-5) mol/l). Incubation for 1, 2 or 7 days resulted in an 80% concentration- and time-dependent reduction in HCSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…RAAS blocking agents thus might influence ET-1 plasma concentrations independent of the actual blood pressure. It was likewise shown that also beta blockers [29, 30] and calcium channel blockers [31-32] alter the paracrine ET-1 system. The majority of the remaining studies reported plasma ET-1 concentrations in treatment naive hypertensive patients, see table 1.…”
Section: Discussionmentioning
confidence: 99%
“…RAAS blocking agents thus might influence ET-1 plasma concentrations independent of the actual blood pressure. It was likewise shown that also beta blockers [29, 30] and calcium channel blockers [31-32] alter the paracrine ET-1 system. The majority of the remaining studies reported plasma ET-1 concentrations in treatment naive hypertensive patients, see table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prostacyclin production has been proposed as an additional vasodilator mechanism of NEB action [16]. Moreover the vasoconstriction factor endothelin-1 has been demonstrated to be suppressed by NEB [35]. Both substances are also regulated by estrogens (for review see [36]) contributing to gender-related differences in vascular tone and therefore being candidates for NEB action.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological effects of nebivolol have been studied in vitro on segments of the thoracic aorta in mice (Broeders et al, 2000;Altwegg et al, 2000); coronary and carotid artery in canide (Ritter, 2001); aorta and small mesenteric arteries in rat and bovine (Cosentino et al, 2002;De Groot et al, 2003;Parenti et al, 2000); human aortic smooth muscle cells (André et al, 2000), coronary endothelium and smooth muscle cells (Brehm et al, 2000(Brehm et al, , 2001. In the current study, we investigated in vivo the potential pharmacological effects of nebivolol (vs. bisoprolol) on the body weight gain of moms during pregnancy, on the arterial pressure, heart rate and blood flow of reproductive tract but also on the vascularization of the uterus of rats.…”
Section: Discussionmentioning
confidence: 99%